INDUKSI MUTASI DAN SELEKSI IN VITRO MENGGUNAKAN ASAM FUSARAT UNTUK KETAHANAN PENYAKIT LAYU PADAPISANG AMBON HIJAU - Lestari, Endang G; Mariska, I; Roostika, I; Kosmiatin, M (BERITA BIOLOGI, 2006)
Due to its high vitamin and nutrition content, banana (Musa paradisiaca L.) is deemed necessary as the mineral resources. The demand on the disease free seedlings are recently increasing. However, facing the problems of Fusarium attack in the production centers, health seedlings in the sufficient number are difficult to be provided. Hence, to solve the problems, mutative induction and in vitro selection to the shoot tip explants has been carried out in banana cv "Ambon Hijau", This research was conducted at the tissue culture laboratory of Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development. On level of 500; 750; 1000; and 1500 rad, Gamma ray radiation have been applied, continued by in vitro selection by using 0, 30 and 45 mg/1 fusaric acid. The selected explant about 0,5 cm were treated for 2 x 4 week selection period. The result showed that the best medium for regeneration was MS basal medium contains 3 mg/1 BA. The irradiation could increase somaclonal variation as well as created some new somaclones that resistant to fusaric acid. However irradiation and in vitro selection caused inhibition of culture growth. The more dosage of irradiation and concentration of fusaric acid decreased regeneration rate of explant. Inoculation by using conidia (5 g/kg soil) provided 18 putative mutant and higher concentration of conidia (lOg/lOkg soil) produced 37 mutant that resistant to Fusarium.